Awareness and Practice of Prevention of Myocardial Infarction among Hypertensive Patients: Cross Sectional Study in a Tertiary Cardiac Centre of Nepal - Adhikari, Asmita; Bhandari, Buna (Nepalese Heart Journal, 2017)
Background and Aims: Hypertension is one of the emerging public health problems in developing country like Nepal. Among complications of hypertension, Myocardial Infarction is most distressing. Although, myocardial infarction is life threatening disease, it is yet preventable. Good knowledge and practice is required for prevention and control of myocardial infarction. Therefore, this study intended to assess knowledge and practice of hypertensive patients regarding prevention of myocardial infarction. Methods: Hospital based cross- sectional study was conducted among ninety-six hypertensive patients in outpatient department of Sahid Gangalal National Heart Centre, Nepal. Purposive sampling method was used to select calculated number of study participants. Data was collected by interview method using structured questionnaire and descriptive and inferential statistics was used to analyze the data. Results: More than half of the participants (60.4%) had high level of knowledge of prevention of myocardial infarction whereas 39.6% had low level of knowledge. Similarly, 57.3% had good practice; however, 42.7% had poor practice. This study found significant association of knowledge with gender, education and socio-economic status. In the same manner, there was significant association of practice with ethnicity and awareness of disease. Conclusion: Only around half of the hypertensive patients had good knowledge and practice of the prevention of myocardial infraction. Therefore, awareness level should be increased and identified factors needs to be addressed. Nepalese Heart Journal 2017; 14(1): 25-28